Surface-enhanced Raman scattering (SERS) spectroscopy in small molecule detection and application - Kao, Ya-Chuan (Nanyang Technological University, 2022)
Surface-enhanced Raman scattering (SERS) spectroscopy is an advanced analytical technique for bioanalysis. However, one of the key challenges that impedes SERS for actual biomolecule detection is due to two reasons: 1) the intrinsically low Raman activities of biomolecules and 2) the lack of interactions between the analyte and plasmonic nanoparticles. The objectives of my thesis is to address these limitations to achieve the practical applications using SERS spectroscopy via platform design and modification of the plasmonic nanoparticles surface chemistry. In chapter 2, we demonstrate a two-part strategy at the oil/water interface to control the single building block morphology over the orientational ordering of supercrystals by tuning surface ligands. In chapter 3 we utilize two types of Ag nanoparticle to form a superhydrophobic SERS detection platform for two urinary metabolites via capture-and confine strategy at the molecule-level. In chapter 4, we follow up the detection strategy from chapter 3 as a proof-of-concept diagnostic kit for spontaneous miscarriage by evaluating the ratio between 5β-pregnane-3α,20α-diol-3α-glucuronide (pregnane) and tetrahydrocortisone (THC). In chapter 5, we further exploit the confine-and-capture strategy for different structural variants analysis. The different binding sites and molecular states of the multiple analytes and probes enable the formation of diversified molecular complexes with different configurations, thus intensifying the specific differences in SERS fingerprints obtained by the various analytes. Lastly, I conclude my thesis with a summary for the different research work and provide an outlook for continuous study in the biomolecule detection and further applications.